Comparative Study on the Kinematic Performance of Front Wheel Drive (FWD) and Rear Wheel Drive (RWD) Vehicles - Ismail, Ahmad Yusuf; Zuntion, Reyhan Bahauddin Ramadhan (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2024)
The automotive industry has continuously innovated drive systems. Among various types, Front Wheel Drive (FWD) and Rear Wheel Drive (RWD) systems are widely used. This research examines the influence of these systems on acceleration and deceleration performance through field tests conducted on public highways. Five speed variations—40, 60, 80, 100, and 110 km/h—were tested for acceleration and deceleration. Results indicate RWD vehicles outperform FWD vehicles in acceleration due to the rear location of the drive wheels, providing superior propulsion. Conversely, FWD vehicles demonstrate better deceleration performance, attributed to shorter braking distances and improved braking efficiency.